2020
DOI: 10.46222/ajhtl.19770720-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tourism Development on the Quality of Life: A case study of Perhentian Island, Malaysia

Abstract: The purpose of this research was to identify the perceptions of the local community toward tourism development impacts on Perhentian Island. Specifically, the research examined the local community’s perceptions of socio-cultural impacts, economic impacts, and environmental impacts of tourism development. The research also examined the relationship between the impacts of tourism development on the local community’s quality of life (QOL). This research was conducted using a quantitative approach by obtaining res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…Rami et al (2019) and Ibrahim et al (2019) found that the development of local tourism can improve the community's welfare. It is consistent with the community's growing socioeconomic status, employment, income, and language proficiency (Nordin et al, 2020). It is asserted that tourist development has a greater positive influence than negative impact; therefore, the existence of tourism development is thought to improve the quality of life of people who reside in local destinations and their sustainability.…”
Section: Correlation Of Cbt With Sustainable Development To Improve C...mentioning
confidence: 62%
See 1 more Smart Citation
“…Rami et al (2019) and Ibrahim et al (2019) found that the development of local tourism can improve the community's welfare. It is consistent with the community's growing socioeconomic status, employment, income, and language proficiency (Nordin et al, 2020). It is asserted that tourist development has a greater positive influence than negative impact; therefore, the existence of tourism development is thought to improve the quality of life of people who reside in local destinations and their sustainability.…”
Section: Correlation Of Cbt With Sustainable Development To Improve C...mentioning
confidence: 62%
“…To strengthen tourist administration and prioritize the socio-cultural circumstances of the community, a wave of tourism with thoughtful and synergistic planning is required (Stone & Stone, 2020). The implementation and development of a community-based tourism model that focuses on the development of local tourism because it utilizes local resources and benefits is the determining factor that can improve the image and positive benefits of tourism (Giampiccoli & Mtapuri, 2020;Müllera et al, 2020;Nordin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Dalam penelitiannya Ibrahim et al (2019) menjelaskan bahwa pengembangan pariwisata lokal dapat meningkatkan kesejahteraan masyarakat, masyarakat setempat ditemukan telah meningkatkan tingkat sosial ekonomi mereka melalui kesempatan kerja; pendapatan tambahan dan keterampilan bahasa. Hasil penelitian dari Nordin et al (2020) menyatakan bahwa Pembangunan pariwisata lebih banyak memiliki dampak positif dari pada dampak negatif, adanya pembangunan pariwisata ini dinilai dapat meningkatkan kualitas hidup masyarakat. Dalam penelitiannya Nordin et al (2020) juga menemukan pengaruh manfaat sosial budaya, manfaat ekonomi, biaya ekonomi, dan manfaat lingkungan memiliki hubungan yang signifikan dengan kualitas hidup, adanya temuan ini sangat penting bagi perencanaan dan pengembangan dalam merencanakan pembangunan pariwisata yang strategis dan berkelanjutan di destinasi pariwisata.…”
Section: Kajian Literaturunclassified
“…Hasil penelitian dari Nordin et al (2020) menyatakan bahwa Pembangunan pariwisata lebih banyak memiliki dampak positif dari pada dampak negatif, adanya pembangunan pariwisata ini dinilai dapat meningkatkan kualitas hidup masyarakat. Dalam penelitiannya Nordin et al (2020) juga menemukan pengaruh manfaat sosial budaya, manfaat ekonomi, biaya ekonomi, dan manfaat lingkungan memiliki hubungan yang signifikan dengan kualitas hidup, adanya temuan ini sangat penting bagi perencanaan dan pengembangan dalam merencanakan pembangunan pariwisata yang strategis dan berkelanjutan di destinasi pariwisata. Meski memiliki banyak dampak positif, pariwisata lokal ini juga memiliki tantangan, oleh karena itu sangat penting untuk memahami sejauh mana kesejahteraan masyarakat di tengah pembangunan pariwisata yang merupakan elemen kunci dalam mewujudkan masyarakat yang berkelanjutan (Ibrahim et al, 2019).…”
Section: Kajian Literaturunclassified
“…Furthermore, recent studies have shown that tourism infrastructure has a positive impact both directly and indirectly on the quality of life of residents through sustainable tourism development (Mamirkulova et al 2020). Therefore, there have been studies related to tourism infrastructure, although this issue is not always entirely the focus of research, such as those considering the role of infrastructure in tourism development (Prideaux 2000;Jovanović and Ilić 2016), infrastructure impact on tourism development (Seetanah et al 2011;, the relationship between infrastructure and tourism (Suleiman and Albiman 2014;Mandić et al 2018), the impact of transport infrastructure on tourism development (Khadaroo and Seetanah 2007a, 2007bSeetanah and Khadaroo 2009;Ouariti and Jebrane 2020), relationship between tourism infrastructure and international visitor flows (Lim et al 2019), and the relationship between foreign direct investment and tourism development (Selvanathan et al 2012;Khoshnevis Yazidi et al 2015;Samimi et al 2017). These studies have shown the impact of infrastructure, or some of its components, on tourism development in various contexts.…”
Section: Introductionmentioning
confidence: 99%